2017
DOI: 10.1017/s1368980017002087
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and factors associated with stunting among infants aged 6 months in a peri-urban South African community

Abstract: The association between stunting and lower birth weight, shorter maternal height and male sex reflects possibly the intergenerational origins of stunting. Therefore, interventions that focus on improving preconceptual and maternal nutritional status, combined with strategies to promote appropriate infant feeding practices, may be an important strategy to prevent stunting in vulnerable settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 38 publications
(53 reference statements)
4
12
0
5
Order By: Relevance
“…Victora et al reported that, since low birthweight is more commonly found in infants whose mothers were stunted, the effect of stunting on cognition may be intergenerational [ 54 ]. Matsungo et al (2017) further reported that boys, who scored lower parent rating scores in our study, were 1.73 times ( p = 0.017) more likely to be stunted than girls [ 49 ]. Higher stunting rates in boys concur with the findings from 16 demographic and health surveys from 10 sub-Saharan countries [ 55 ].…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Victora et al reported that, since low birthweight is more commonly found in infants whose mothers were stunted, the effect of stunting on cognition may be intergenerational [ 54 ]. Matsungo et al (2017) further reported that boys, who scored lower parent rating scores in our study, were 1.73 times ( p = 0.017) more likely to be stunted than girls [ 49 ]. Higher stunting rates in boys concur with the findings from 16 demographic and health surveys from 10 sub-Saharan countries [ 55 ].…”
Section: Discussionsupporting
confidence: 51%
“…We found that stunted, as well as infants born with a low birthweight scored lower psychomotor scores. In the same study population, Matsungo et al (2017) reported that birth weight (kg) was inversely associated with stunting [ 49 ], which may be a consequence of maternal short stature, combined with poor nutrition during pre-conception and pregnancy [ 50 , 51 , 52 , 53 ]. Victora et al reported that, since low birthweight is more commonly found in infants whose mothers were stunted, the effect of stunting on cognition may be intergenerational [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, a significantly higher proportion of IUH was underweight at three months (8.2% vs 1.6%) and stunted at three and six months (44.9% vs 3.96%; 20.9% vs 4.84%) when compared to their IEH counterparts. Other South African studies have also reported a high prevalence of stunting in children (28.5%) [21,22]. Although a larger proportion of the IUH were breastfed for less than six months, stunting and being underweight were independent of breastfeeding duration.…”
Section: Discussionmentioning
confidence: 76%
“…Hasil yang sama ditunjukkan pada penelitian di Afrika Selatan yang melaporkan bahwa waktu pemberian ASI eksklusif tidak memengaruhi kejadian stunting. 12 Penelitian lainnya menyebutkan bahwa tidak terdapat hubungan yang bermakna antara pemberian ASI eksklusif dengan kejadian stunting, wasting, maupun underweight. 13 Subjek penelitian ini berusia 12-23 bulan sehingga pemenuhan gizi utama anak didapatkan dari MPASI.…”
Section: Metodeunclassified